The Service Delivery and Customer Relation Management In Increasing the Customer Value - Pandjaitan, Dorothy R. H. (Business and Management Review, 2012)
Banking services can not be separated from customer in which banking service delivery is used as a common yardstick to evaluate the service delivery and how well the customer relation is managed by the bank. Bank is required to deliver its service in order to maintain its customer loyalty and to increase customer value. The objective of this research is to analyze the influence of service delivery and customer relation management toward customer value. The subjects of this research are customers of “Siger Mas” and the “Simpeda” savings of Bank of Lampung. Three sub variables consisting of the level supporting physical availability, the supporting conveniences facilities, and personal contacts were employed to measure the service performance. Three sub variables consisting of the process of creating the customer value, responsibility, and process product in another hand are used to measure customer relation management. Customer value was measured by the benefit indicators and sacrifice burden of the customers. It was succeeded to collect data from a total of 431 respondents consisting of all customers of the “Sigermas” and the “Simpeda” Savings from five branches and headquarter of Bank Lampung. Result shows that service delivery and customer relation management influence customer value. However, service delivery has stronger influence than the customer relation management. Keywords: service delivery, customer relation management, customer value, customer loyalty. DAFTAR PUSTAKA Brandy, Michael K., 1999, “An Explanatory Study of Service Value in The USA and Equador”. International Journal of Service Industry Management. Vol.10. Christopher, Martin; Payne, Adrian, Ballantyne, David, 2010, Relationship Marketing: Bringing Quality, Customer Service and Marketing Together, Jordan Hill, Butterwoorth Heinemann. Curry, Jay, Adam, 2000, The Customer Marketing Method: How to Implement and Profit from Customer Relationship Management, Free Press, New York.Garbarino, Ellen, Marks Johnson, 1999, “The Different Rules of Satisfaction, Trust and Commitement in Relationship”, Journal of Marketing, Vol.63. Gronroos, C., 2001, Service Management and Marketing, First Edition, Maxwell MacMillan Publishing, Singapore. Hair, F., Joseph Jr; Robert Bush, P., David Ortinau J., 2000,  Marketing Research, Within a Changing Information Environment, MacGraw Hill. Hughes, Althur Middleton, 2003, The Customer Loyalty Solution, What Works (and what doesn’t) in Customer Loyalty Programs, MacGraw Hill. Kotler, Phillip and Amstrong, 2003, Marketing Management, The Millenium Edition, Prentice Hall. Kotler dan Keller, 2009, Marketing Management: Analysis, Planning, Implementation and Control, New Edition, Prentice Hall International Inc, New Jersey. Palmer, Adrian, 2001, Principles of Service Marketing, MacGraw Hill International, USA. Pandjaitan, Dorothy Rouly, 2005, Pengaruh Ekuitas Merek terhadap loyalitas pelanggan pada nasabah bukan PNS di Bank Lampung, Tesis, Fakultas Ekonomi Padjajaran. Riza A.N., Rukmana, 2005, “Pengaruh Tuntutan Pelanggan dan Kinerja Bauran Pemasaran Jasa terhadap Nilai Pelanggan serta Dampaknya pada Pengguna Jasa Telekomunikasi”, Jurnal Informasi dan Pemasaran, Vol VII No.21. Edisi April 2005. Rust, Roland. Antony Zahorik, 2000, Customer Satisfaction, Customer Retention and Market Share, Journal of Service Marketing, Vol. 13. No.2 Sirdeshmukh, Deepak, Jagdip Singh, and Barry Sabol, 2002, “Customer Trust, Value, and Loyalty in Relationship Exchange”, Journal of Marketing, Vol.66. Sugiono Aritonang, 2008, Pengaruh kinerja ekuitas merek dan Customer Relationship Management terhadap keunggulan bersaing dan dampaknya terhadap loyalitas pelanggan (survey pelanggan mobil di Jabodetabek), Fakultas Ekonomi Program Doktor Pascasarjana Universitas Padjajaran, Bandung. Zeithaml, A., Valerie A., Parasuraman A., Berry L., Leonard, 2010, Delevering Quality Service: Balancing Customer Perceptions and Expectations, The Free Press, New Jersey. Zeithaml, A., Valerie A., Mary Jo Bitner, 2010, Service Marketing, Integrating Customer Focus Across the Firm, MacGraw Hill.